The strength characteristics of elite and subelite female Gaelic football players (The Journal of Strength and Conditioning Research, 2024)
There is currently an underrepresentation of sports science research focused on the female athlete, specifically in the context of Gaelic football. The aims of this study are to (a) compare the strength characteristics of elite and subelite players and (b) establish normative-based values and percentile scores for the strength characteristics of female Gaelic football players. Ninety-two female Gaelic football players were recruited for this study and subsequently categorized as elite (intercounty n = 30, age; 25.1 ± 5.3 years, stature; 1.69 ± 0.06 m, mass; 69.5 ± 5.9 kg) or subelite (club n = 62, age; 25.4 ± 6.8 years, stature; 1.66 ± 0.06 m, mass; 65.1 ± 8.9 kg). The physical strength characteristics of the subjects were assessed through the isometric midthigh pull (IMTP), countermovement jump (CMJ), and 10-5 repeated jump test. Statistically significant differences were found in the physical strength characteristics between the groups with elite players demonstrating greater peak force (large effect), relative peak force (moderate effect), and reactive strength index (large effect). Statistically significant differences were also observed for key CMJ phase characteristics with elite players producing greater RSImod (moderate effect), jump height (large effect), and propulsion peak power (large effect) than subelite players. This study demonstrated that there are moderate to large differences between playing standards with elite players displaying superior reactive-, explosive-, and maximal-strength than their subelite counterparts. The strength characteristics evaluated in this study may be used in conjunction with other performance indices to distinguish between elite and subelite playing standards in female Gaelic football players.